2019
DOI: 10.26833/ijeg.404426
|View full text |Cite
|
Sign up to set email alerts
|

Outlier detection of land surface temperature: Küçükçekmece Region

Abstract: Unplanned and rapid urbanization is one of the reasons for the rising surface temperature values in urban areas. There is a considerable amount of literature demonstrating the association of urbanization with surface temperatures. Küçükçekmece Lake, an important lake which has been meeting utility water needs of Istanbul, and unplanned and rapid urbanization around it have been affected by this inevitable change for years. Although surface temperatures generally correlate strongly with each other, very high an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…With the developing satellite technologies, it is possible to determine the urban heat islands with the thermal sensors on the satellite (Orhan et al 2019). Today many studies are investigating the relationship between urban land use/land cover and urban heat island (Herbei et al 2012;Patil et al 2018;Khorrami et al 2019;Kuşak and Küçükali 2019). When these studies were examined, it was observed that generally similar results were obtained.…”
Section: Introductionmentioning
confidence: 89%
“…With the developing satellite technologies, it is possible to determine the urban heat islands with the thermal sensors on the satellite (Orhan et al 2019). Today many studies are investigating the relationship between urban land use/land cover and urban heat island (Herbei et al 2012;Patil et al 2018;Khorrami et al 2019;Kuşak and Küçükali 2019). When these studies were examined, it was observed that generally similar results were obtained.…”
Section: Introductionmentioning
confidence: 89%
“…For the purposes of this study, the LST calculation method created by Shen and employed in the prior study (Kusak & Kucukali, 2018 ) was preferred. In this case, emissivity values of 0.9923 are approved for water areas, 0.923 are allowed for urban impermeable and bare soil regions, and 0.986 are accepted for plant areas.…”
Section: Methodsmentioning
confidence: 99%
“…If FB <DB, then the shading of the building exposed to the sun is formed in the neighboring garden area or the back-garden area between the neighboring buildings (Arumi-Noe, 1996; Data, 2001;(Kuşak and Küçükali, 2019)).…”
Section: Bc=ab/tany1=ab*tanz1mentioning
confidence: 99%
“…In Turkey, because summer days are long and the weather is too hot, shady places are desired for getting rid of the sun's overwhelming effect. In order to ensure that buildings or open-air rest areas are kept in the shade, they can be designed with buildings or recreation areas at the planning stage (Kuşak and Küçükali, 2019;Ekercin et al, 2019). Positioning the specified spaces in the maximum amount of shade is closely related to the location of the buildings, the distance between the buildings, the sun's azimuth angle and the solar zenith angle, as well as the time of the day and the sun declination angle at that time.…”
Section: Introductionmentioning
confidence: 99%